ICO - Stijn Van Hijfte (Blockchain and Regulation, 2021)
Purpose Infectious keratitis has a profound impact on patients quality of life (QoL). Patient-reported outcome measures (PROMs) provide an invaluable method to capture subjective patient experiences and support practitioners in health care delivery. The primary and secondary objectives of this review were to systematically evaluate PROM tools used in infectious keratitis and evaluate the quality and content of PROMs in use for infectious keratitis. Methods The protocol implemented for review was published in PROSPERO (CRD42023464686). A literature review was performed in PubMed, MEDLINE OVID, Embase OVID, Cochrane, Scopus, Web of Science, and PsycINFO in October 2023. Full-length studies, published in English, featuring named and externally validated PROMs which were used to evaluate QoL outcomes of patients with infectious keratitis, were included. Nonvalidated PROMs used in patients with infectious keratitis were excluded. Studies including but not explicitly defining corneal pathologies were also excluded. Psychometric quality, validity, and risk of bias of each PROM were assessed using previously validated criteria. Results Eight studies evaluated PROMS in infectious keratitis, with 8 different PROMs (1 generic, 7 ophthalmic but not keratitis-specific) used. Patients with infectious keratitis demonstrated impaired QoL in all PROMs, domains representing vision and visual function most impaired. Dependence, mobility, and mental and emotional state were also affected. Only 1 paper (13%) used psychometric analysis to validate the PROMs before use. Conclusions Infectious keratitis has a negative impact on patient's QoL, across multiple domains. A variety of PROMS have been used to assess QoL in keratitis with most awaiting validation for infectious keratitis.